HYPNOSOSMN.MP3: ALAT HIPNOSIS UNTUK MEMBANTU ORANG-ORANG DENGAN KESULITAN TIDUR - Suharya, Fitra; Varesty, Vonnie; Agia, Muhamad Irfan; Aprilia, Gerizcha (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Sleep is a natural process for releasing physical fatigue and mental fatigue. Sleep difficulty is a condition where a person has difficulty in penetrating sleep phase so she stays awake when she wants to sleep. Individual with sleep difficulty can overcome her problem by consuming sleeping pills, relaxation massage, or the services of a professional hypnotherapist. Although effective, sleeping pills can cause negative impact in the long-term. Likewise with reflexology, though not causing side effects, it is less effective and less flexible. One of the new way is to use the proposed new